2002
DOI: 10.1103/physrevlett.89.017402
|View full text |Cite
|
Sign up to set email alerts
|

Large Four-Wave Mixing of Spatially Extended Excitonic States in Thin GaAs Layers

Abstract: We study the size dependence of the nonlinear response of weakly confined excitons for the size region beyond the long wavelength approximation regime. The observed degenerate-four-wave mixing signal of GaAs thin layers exhibits an anomalous size dependence, where the signal is resonantly enhanced at a particular thickness region. The theoretical analysis elucidates that this enhancement is due to the size-resonant enhancement of the internal field with a spatial structure relevant to the nondipole-type excito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 80 publications
(63 citation statements)
references
References 17 publications
1
62
0
Order By: Relevance
“…On the other hand, the scattering spectra of the thin film are significantly modified from the bulk ones, and we found that they reflect the exciton-photon coupled modes in the thin film. 17,18,21,33,35 Therefore, the RHPS measurement is also useful to observe the exciton-photon coupled modes in nano-structured materials 34 as well as the four-wave mixing 17,29,35 and the two-photon excitation scattering. 33 We also found that semiconductor thin films have much degrees of freedom to control generated states of entangled photon pairs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, the scattering spectra of the thin film are significantly modified from the bulk ones, and we found that they reflect the exciton-photon coupled modes in the thin film. 17,18,21,33,35 Therefore, the RHPS measurement is also useful to observe the exciton-photon coupled modes in nano-structured materials 34 as well as the four-wave mixing 17,29,35 and the two-photon excitation scattering. 33 We also found that semiconductor thin films have much degrees of freedom to control generated states of entangled photon pairs.…”
Section: Discussionmentioning
confidence: 99%
“…11,50-52 Moreover, optical responses explicitly reflects the confinement of center-of-mass motion of excitons in nano-structured materials and also in the nanoto-bulk crossover regime, [17][18][19][20][26][27][28][29][30][31][32][33][34][35][36] which we investigate in the present paper.…”
Section: 43mentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, a wave-wave coupling between excitons and radiation occurs, and their interaction volume becomes considerably larger, especially for multipole-type excitons with the CM quantum number λ ≥ 2, leading to large radiative corrections. As a result, the nonlinear optical responses are enhanced [29][30][31] , and the level shift and radiative decay rate are resonantly increased [32][33][34] with the sample size. We should note that such a large interaction volume also strengthens the coupling between different components of excitons via radiation.…”
Section: Introductionmentioning
confidence: 99%
“…The real part Re[ ω ξ ] gives the eigenenergy including the radiative shift and the imaginary part −Im[ ω ξ ] gives the radiative width. An increase in the film thickness leads to a large interaction volume between excitonic waves and radiation waves, and their phase-matching leads to the large radiative correction from the bare excitonic states especially in a nano-to-bulk crossover size regime [30][31][32][33][34] .…”
Section: Thin Filmmentioning
confidence: 99%